THE MODELING OF THE EFFECT OF CAREER PLATEAU ON WORK ATTITUDE - Rauly Sijabat (Jurnal Bisnis Manajemen, 2023)
Work attitude which includes job satisfaction, work commitment and turnover intention is an important issue in the management and development of human resources in a company. One of the important factors that shapes work attitude is career growth opportunities. However, because of the pyramid shape in the company's career system, many employees experience career plateau. The results of empirical testing regarding the effect of career plateau on work attitude also still show inconclusive results. Based on these phenomena, this study examines the effect of career plateau, job satisfaction, work commitment and turnover intention which was developed in an empirical model. The testing of the research model and the influence among variables was carried out using empirical data from the employee respondents from various fields of work, such as banking, education, consultant, construction, garment, karoseri and food. The findings from statistical tests conducted in this study indicate that the career plateau can decrease the employee job satisfaction and work commitment but can increase turnover intention. The results of this study also show that job satisfaction and work commitment can reduce the employee turnover intention.